2019
DOI: 10.1038/s41598-018-37036-1
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-based transfection enhances RNAi and CRISPR-mediated mutagenesis in non-model nematode systems

Abstract: Nematodes belong to one of the most diverse animal phyla. However, functional genomic studies in nematodes, other than in a few species, have often been limited in their reliability and success. Here we report that by combining liposome-based technology with microinjection, we were able to establish a wide range of genomic techniques in the newly described nematode genus Auanema. The method also allowed heritable changes in dauer larvae of Auanema, despite the immaturity of the gonad at the time of the microin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 72 publications
(69 reference statements)
0
43
0
Order By: Relevance
“…In addition, lipofectamine was added to the microinjection mix to improve delivery of the CRISPR components across cell membranes. The Rol phenotype was then observed in a subset of the F 1 progeny of the microinjected females and a subset of the microinjected iL3s (Adams et al, 2019). These results demonstrate that mutant phenotypes can be induced directly in infective larvae through the inclusion of lipofectamine in the microinjection mix, and raise the possibility that a similar approach could be applied to other mammalian-parasitic nematodes such as hookworms that lack a free-living adult stage.…”
Section: Crispr/cas9-mediated Targeted Mutagenesis In Parasitic Nematmentioning
confidence: 73%
See 1 more Smart Citation
“…In addition, lipofectamine was added to the microinjection mix to improve delivery of the CRISPR components across cell membranes. The Rol phenotype was then observed in a subset of the F 1 progeny of the microinjected females and a subset of the microinjected iL3s (Adams et al, 2019). These results demonstrate that mutant phenotypes can be induced directly in infective larvae through the inclusion of lipofectamine in the microinjection mix, and raise the possibility that a similar approach could be applied to other mammalian-parasitic nematodes such as hookworms that lack a free-living adult stage.…”
Section: Crispr/cas9-mediated Targeted Mutagenesis In Parasitic Nematmentioning
confidence: 73%
“…Another recent study used CRISPR to target the S. stercoralis homolog of the C. elegans collagen gene rol-6 (Adams et al, 2019). The CRISPR components were introduced by microinjection into either free-living females or iL3s.…”
Section: Crispr/cas9-mediated Targeted Mutagenesis In Parasitic Nematmentioning
confidence: 99%
“…Toward this, we have identified the orthologs of 16 main sex determination genes, including tra-1/2 , gld-1 , her-1 and fem-1/2 (Table S5), which are clear candidates to investigate the sex determination mechanisms in A. rhodensis . In parallel, we are developing reverse genetic and functional genomic technologies for these species, and these promise routes to rapid validation of hypotheses of gene function (Adams et al 2019). The A. rhodensis sex determination system may integrate genetic, maternal, environmental and random components, and this nexus of interacting components will also become amenable to manipulation and dissection.…”
Section: Discussionmentioning
confidence: 99%
“…The RNAi mixture was produced by combining 5 µl of Arh-g5747 siRNA (approximately 100 ng), 4 ul of M9 buffer (Stiernagle 2006) and 1 µl (10% v/v) LipofectamineRNAiMax reagent (Invitrogen) and incubating at 25° for 20 min. Previously, we have shown that inclusion of the transfection reagent Lipofectamine dramatically improves RNAi efficiency in A. rhodensis (Adams et al 2019). For control injections Arh-g5747 siRNA was omitted from the mixture and replaced with additional M9 buffer.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to these “hands-off” approaches to gene transfer, it is also possible to transfer CRISPR/Cas9 elements into pre-parasitic larvae of soil-transmitted parasites by microinjection (Adams et al, 2019). Mutations were targeted to the rol-6 ortholog in S. stercoralis by microinjecting a nucleoprotein comprising Cas9 and a target specific gRNA along with lipofectamine into the body cavities of iL3.…”
Section: Future Directions In Transgenesis For Parasitic Nematodesmentioning
confidence: 99%